Sistem Kontrol Stop Kran Otomatis Berdasarkan Deteksi Kebocoran Pipa Air Rumah Tangga Berbasis Arduino - Jefrina Dian Stifvani; Yudi Kristyawan; Edi Prihartono (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
Water is an essential resource for every household. Typically, household water distribution systems rely on PVC pipes and faucets. Despite this, water leakage remains a frequent issue, occurring in both pipes and taps. This study aims to design an Arduino-based automatic faucet control system capable of detecting leaks in water pipes, with the goal of conserving water and improving usage efficiency. The system employs a pressure sensor to monitor water pressure within the pipe, an ultrasonic sensor to detect user presence at the tap, and a solenoid valve to automatically shut off the water supply in the event of a leak. Testing and design outcomes indicate that the system functions effectively. The solenoid valve successfully closes the water flow automatically when a leak is detected. However, the current system lacks a notification feature to alert users when a leak occurs. Future developments should consider integrating a notification mechanism to inform users promptly about any detected leaks.